EVALUATION OF SEED NUT SIZE AS INDEX OF SELECTION FOR SUPERIOR SEED QUALITY ATTRIBUTES IN TWO BIOTYPES OF CASHEW (ANACARDIUM OCCIDENTALE) - Kehinde, T. O.; Adebisi, M. A.; Alegiledoye, A. O.; Shofuyi, K. A. (Plant Breeding and Seed Science, 2015)
Quality seed nuts are germane to propagation of the cashew plant. Seed nut fraction and genotypes have been identified to influence seed quality of crop plant. Unexpectedly, seed size effect has not been well documented in Brazilian and local biotypes of cashew grown in Nigeria. An experiment was initiated to investigate the effect of three nut sizes and two biotypes of cashew on seed quality (physical and physiological) traits. Seed nut were collected from three cashew plants of the same age of each of the biotypes and were allowed to stay for 60 days after collection. The experiment was carried out in a factorial arrangement laid out in a completely randomized design with three replicates using two factors (nut size and biotypes) in 2011 cropping season in both laboratory and screen house tests. Data were collected on physical characters such as seed length, seed width, 100 seed weight and seed imbibition rate while physiological characters were seed germination and early vigour traits. Data obtained were analysed statistically using Tukey HSD test at 5% probability level. The result revealed that some of the characters were significantly different from one another. Seed nut fraction and biotype had considerable effect on seed length, seed width, seed imbibition rate and 100 seed weight. The two factors (nut size and biotype) interaction had profound effect on seed width only. On seed physiological quality, biotype effect was significant on seedling fresh and dry weights and seedling growth rate whereas seed nut size had considerable effect on seed germination, seedling vigour index, seedling fresh weight and seedling growth rate. The interaction effect of nut size and biotype recorded significant effect on the above four characters. Brazilian biotype had superior physical characters (seed length, width and weight) but with low imbibitions rate while medium and large nut sizes gave the highest seed germination and seedling vigour. Also, medium and large nuts had the highest seedling fresh weight whereas the highest seedling growth rate was recorded with small size seed. However, large, medium and small nut sizes of local biotype had the highest imbibition rate, whereas small, medium and large nut size of Brazilian biotype gave the highest 100 seed weight. On seedling emergence, large nuts of local biotype recorded the highest seedling emergence and seedling vigour index. Medium nuts of the two biotypes of cashew are recommended for cashew seed multiplication. Further research on physiology of cashew nut sizes during storage and osmo and hydro priming treatment effect are necessary and therefore advocated.